Effect of mobile app-based oral hygiene instructions on clinical parameters, oral bacterial diversity, and composition of subgingival microbiota in periodontitis patients - Melinda Rabekka Purba; Mardikacandra Manggala Putra; Benso Sulijaya; Adityo Widaryono; Valdy Hartono; Yoga Setiadharma; Aurelle Khadeeja Rizany; Fatimah Maria Tadjoedin; Marie Rossini Carmela T. Lachica (Journal of Oral Microbiology)
Introduction Oral hygiene instruction (OHI) is essential during periodontitis treatment. Various OHI approaches have been explored, including mobile apps.Objective To evaluate the mobile app-based OHI’s effect on periodontitis management by analyzing clinical parameters and subgingival microbiota.Methods Forty-four periodontitis patients were randomly assigned into two groups. The test group (n = 22) received scaling and root planing (SRP), OHI, and mobile app-based OHI, whereas the control group (n = 22) received SRP and OHI. Full mouth plaque score (FMPS), bleeding on probing (BOP) and probing pocket depth at the sampling sites (site-PPD) were assessed at baseline, one- and three-month visits. The 16S rRNA next-generation sequencing (NGS) was used to analyze subgingival plaque samples.Results Significant reduction in FMPS, BOP, and site-PPD at one- and three-month visits compared to baseline (p < 0.001) with no significant differences across groups (p > 0.05). In test groups, intra-group analysis showed better improvement in BOP and site-PPD (p < 0.05) than control. The diversity and composition of subgingival microbiota did not differ between groups or timepoints (p > 0.05).Conclusions Mobile app-based OHI showed no superior effects on improving clinical parameters and subgingival microbiota compared to conventional OHI. Further investigation into its long-term impact on periodontitis treatment is needed.